Effects of adenosine receptor agonists of the A1, A2A and A3 subtypes on the proinflammatory activity of human neutrophils in vitro - Anderson, Ronald (University of Pretoria, 2013)
Thesis (DPhil (Medical Immunology))--University of Pretoria, 2006.